2021
DOI: 10.1126/sciadv.abi7410
|View full text |Cite
|
Sign up to set email alerts
|

Solution-shearing of dielectric polymer with high thermal conductivity and electric insulation

Abstract: Polymer dielectrics, an insulating material ubiquitous in electrical power systems, must be ultralight, mechanically and dielectrically strong, and very thermally conductive. However, electric and thermal transport parameters are intercorrelated in a way that works against the occurrence of thermally conductive polymer electric insulators. Here, we describe how solution gel-shearing-strained polyethylene yields an electric insulating material with an outstanding in-plane thermal conductivity of 10.74 W m −1 K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Similarly, Ronca et al [ 22 ] fabricated PE films with the reduced number of entanglements by uniaxially and biaxially stretching in the solid-state without any solvent, and the increase of k showed two separate regimes which was attributed to the initial crystal orientation and subsequent chain extension. Recently, Ren et al [ 78 ] reported a very simple solution gel-shearing method to fabricate PE films with an in-plane k of 10.74 W (mK) −1 , which is ascribed to the alignment and close packing of ultrahigh-molecular weight crystalline chains, facilitating the formation of separated nanocapacitor with high k (Fig. 6 b).…”
Section: High-performance Thermally Conductive Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Ronca et al [ 22 ] fabricated PE films with the reduced number of entanglements by uniaxially and biaxially stretching in the solid-state without any solvent, and the increase of k showed two separate regimes which was attributed to the initial crystal orientation and subsequent chain extension. Recently, Ren et al [ 78 ] reported a very simple solution gel-shearing method to fabricate PE films with an in-plane k of 10.74 W (mK) −1 , which is ascribed to the alignment and close packing of ultrahigh-molecular weight crystalline chains, facilitating the formation of separated nanocapacitor with high k (Fig. 6 b).…”
Section: High-performance Thermally Conductive Filmsmentioning
confidence: 99%
“…6 b). In brief, a shearing rod drags the UHMWPE solution gel across a heated substrate while driving the gel solution between the rod and the substrate, and then the UHMWPE film is formed and peeled off from the glass substrate at room temperature [ 78 ]. The used solution gel-shearing process is more facile than widely used ultradrawing process.…”
Section: High-performance Thermally Conductive Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Thermally conductive polymers will open up new avenues toward advanced thermal management applications such as chip packaging, soft robotics, and organic light-emitting diodes. 9,14,21,24,25,28,29,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] Conventional conjugated polymers (e.g., polythiophene), composed largely of conjugated carbon-carbon double bonds, possess characteristically low thermal conductivity on the order of ∼0.1 W m −1 K −1 ; notably, graphene is also composed of conjugated carbon-carbon double bonds. 6,8 Graphene is one of the best thermal conductors with thermal conductivity greater than ∼2000 W m −1 K −1 .…”
Section: Introductionmentioning
confidence: 99%
“…9,21–35 Thermally conductive polymers will open up new avenues toward advanced thermal management applications such as chip packaging, soft robotics, and organic light-emitting diodes. 9,14,21,24,25,28,29,36–49…”
Section: Introductionmentioning
confidence: 99%